1986
DOI: 10.1097/00004032-198605000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Population Characteristics and Absorbed Dose to the Population From Nuclear Medicine

Abstract: Those in the U.S. population who receive nuclear medicine examinations have been characterized by age and sex. Males received 42% of examinations while females received 58%. More than one-third of the examinations were done on persons older than 64 y of age and more than two-thirds on patients older than 45 y of age. The per caput effective dose equivalent from nuclear medicine procedures in 1982 was 140 muSv (14 mrem); whereas, the per caput age-specific effective dose equivalent to the U.S. population was 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…This effective dose equivalent value is comparable to the average effective dose equivalent per patient from nuclear medicine studies as reported from surveys in the United States and Europe [17,18].…”
Section: Discussionsupporting
confidence: 75%
“…This effective dose equivalent value is comparable to the average effective dose equivalent per patient from nuclear medicine studies as reported from surveys in the United States and Europe [17,18].…”
Section: Discussionsupporting
confidence: 75%
“…The administered activity of 131 I-sodium iodide for thyroid imaging before the mid-1970s was about 1.85 MBq (Harper et al 1965; Wagner 1968; Atkins 1975; McAfee and Subramanian 1984; Drozdovitch et al 2014), then gradually increased to 3.7 MBq (Sodee and Early 1975; Irwin et al 1978; Mettler et al 1986; Sisson 1997). The administered activity of 123 I-sodium iodide for thyroid imaging before the late-1970s was estimated to be 3.7 MBq (Robertson 1982; Wagner et al 1986), then gradually increased to 11.1 MBq in the 1980s (Mettler and Guiberteau 1983, Mettler et al 1986; Wagner et al 1995; Park et al 1994, 1997) and to 14.8 MBq in the mid-1990s (Mettler and Guiberteau 1998; Becker et al 1999; Kowalsky and Falen 2004; Balon et al 2006a; Joyce and Swihart 2011). The administered activity of 99m Tc-pertechnetate for thyroid imaging before the late-1970s was estimated to be 74 MBq (Early et al 1969; Maynard 1971; Barrall and Smith 1976), then increased to 185 MBq in the 1980s (Mettler et al 1986; Wagner et al 1986; NCRP 1996) and to 222 MBq in the mid-1990s (Mettler and Guiberteau 1998; Becker et al 1999; Kowalsky and Falen 2004; Balon et al 2006a; Joyce and Swihart 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Activities of radiopharmaceuticals administered to adult patients for brain imaging were the following (Table 2): 26 MBq of 197, 203 Hg-chlormerodin (Silver 1968; Maynard 1971; Sodee and Early 1972; Drozdovitch et al 2014);463 MBq 99m Tc-pertechnetate before the early 1970s, then gradually increasing to 555 MBq and to 740 MBq since the mid-1970s (Harper et al 1965; Maynard 1969; Blahd 1971; O’Mara and Mozley 1971; Ramsey and Quinn 1972; Sodee and Early 1972; Brownell et al 1974; Fischer and McKusick 1975; Holman 1976; Mettler and Guiberteau 1983, 1998; Mettler et al 1986; Dahnert 2007);740 MBq of 99m Tc-DTPA, 99m Tc-GH, 99m Tc-HMPAO, and 99m Tc-ECD (USDHEW, 1976; Robertson 1982; Mettler et al 1986, 2008a, 2008b; McAfee 1989; Larar and Nagel 1992; Kuni and duCret 1997; Mettler and Guiberteau 1998, 2012; Donohoe et al 2003a, 2012; Kowalsky and Falen 2004; Dahnert 2007; Juni et al 2009; NCRP 2009; Bonte et al 2011;);111 MBq of 201 Tl-chloride (Saha et al 1994; Kahn et al 1994; Kowalsky and Falen 2004);555 MBq of 18 F-FDG (Kowalsky and Falen 2004; Mettler et al 2008a; Waxman et al 2009; Mettler and Guiberteau 2012). …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the typical number of patients per month cannot necessarily be generalized to smaller institutions since the data are representative only of the relatively large size of institutions represented by the participants. Typical administered activities presented in Table 1 and Table 2 were derived from the literature (Beierwaltes et al 1957; Fields and Seed 1957; Blahd et al 1958; King and Mitchell 1961; Reba et al 1962; Wagner 1968; Belcher and Vetter 1971; Maynard 1971; Sodee and Early 1972; Mettler et al 1986; Wagner 1995) and discussed by the focus group participants.…”
Section: Resultsmentioning
confidence: 99%